Study Of the Structural-Mechanical and Rheological Properties of The Polymer Composition (Eurasian Scientific Herald, 2022)
The article investigates the degree of thixotropic reduction, yield stress and viscosity of sizing polymer compositions based on rice starch, hydrolyzed acrylic emulsion and hydrolyzed polymethyl acrylate. It is shown that the introduction of an acrylic emulsion and hydrolyzed polymethyl acrylate into the composition of the sizing polymer composition improves its rheological properties. The results of experiments on studying the effect of GAE and GPMA, which are part of the sizing composition, on the structural and mechanical properties of starch solutions are presented.